Comparison of Steel Construction Costs Between AHSP and Conventional Method at Padalarang Bandung Steel Warehouse - Palamba, Widsri; Dermawan, Hans (Journal of Engineering Education and Pedagogy, 2025)
Estimating costs too high can burden the project budget, while estimating costs too low can lead to budget shortfalls during implementation. Therefore, optimal planning is necessary, one of which is by comparing construction cost estimates using the AHSP method with conventional calculations from consultants to provide insights into the accuracy and efficiency of both methods in the context of a steel warehouse project. Steel construction has many advantages such as shorter construction duration, a high strength-to-weight ratio making the structure lighter yet still strong, and so on. The research method uses quantitative analysis to estimate the budget plan for steel work by referring to AHSP Cipta Karya and Housing SE Director General of Construction Development No. 68/SE/Dk/2024 and comparing it with the estimates from the consultant. The calculation results show that the more economical estimate for the steel construction work is the conventional calculation from the consultant. The calculation results show that the AHSP estimate is approximately 30.16% higher. This is due to the higher material and equipment costs in the AHSP compared to the consultant's estimate. The suggestion for further research is to conduct calculations on other works, to show the overall construction costs.